Tipping point-induced abrupt shifts in East Asian hydroclimate since the Last Glacial Maximum - Fuzhi Lu; Huayu Lu; Yao Gu; Pengyu Lin; Zhengyao Lu; Qiong Zhang; Hongyan Zhang; Fan Yang; Xiaoyi Dong; Shuangwen Yi; Deliang Chen; Francesco S. R. Pausata; et al. (Nature Communications)
Abstract Multiple tipping points in the Earth system could be triggered when global warming exceeds specific thresholds. However, the degree of their impact on the East Asian hydroclimate remains uncertain due to the lack of quantitative rainfall records. Here we present an ensemble reconstruction of East Asian summer monsoon (EASM) rainfall since the Last Glacial Maximum (LGM) using nine statistical and machine learning methods based on multi-proxy records from a maar lake in southern China. Our results define five tipping points in the EASM rainfall since the LGM, which are characterized by abrupt and irreversible regime shifts with a median amplitude of 387 ± 73 mm (24 ± 5 %). Combined with multi-model simulations and existing records, we attribute these tipping points to cascades of abrupt shifts in the Atlantic meridional overturning circulation (AMOC) and Saharan vegetation. Our findings underscore the nonlinear behavior of the EASM and its coupling with other tipping elements.